Simulation Research of Electric Locomotive Cab Side-window Glass’s Sound Insulation - YANG Xiao-rong; MIN Yang-chun (机车电传动)
Side-window glass SEA simulation model of electric locomotive cab was built with the noise simulation software VA one, and sound insulation of different-thickness single-layer glass, different-thickness intermediate-air layer hollow glass and laminated glass were analyzed by simulation and test. The simulation results showed that the laminated glass had the best sound insulation effect.